(untitled) (Journal of the College of Basic Education, 2022)
Research community: The research community is the community that the researcher aims to study and generalize the results of the research on all its vocabulary. 30/) The date of the cessation of electoral propaganda, as a field of study in view of what the Afaq-Baghdad channel constitutes of the diversity of its ideologies and the difference in its contents, the first as the spokesman for the State of Law Coalition list that represents the government and the second as the spokesman for the Accordance Front, which represents the Islamic Party). It was subjected to analysis in the two channels (13) programs, and the titles and news bulletins were excluded due to the lack of search capabilities in them, due to the repetition of the news content in both channels (")